Маловідомі портрети Феліціяна Лобеського - Купчинська, Л. (Народознавчі зошити, 2014)
Висвітлюється творчість Феліціяна Лобеського, художника західноукраїнських земель першої половини — середини ХІХ ст. Розглянуто рисунки, які він виконав на підставі живописних мистецьких пам’яток попередніх століть.
Висвітлено індивідуальний внесок митця у вирішення актуальних проблем часу. The article has presented some results of studies in creative
works by Felicjan Lobesky, an artist of Western Ukrainian origin
who lived and worked in Galicia, incl. Lviv during the first
half of XX c. Under analysis have been put drawings performed
on the basis of pictorial artistic monuments of previous
centuries. The artworks have been considerd in the context of
multidimensional program of studies in nation’s spiritual and
material culture. Individual artist’s contributions to the solution
of pressing needs of the time have been outlined. Статья посвящена творчеству Фелициана Лобеского, западноукраинского художника первой половины и середины
ХІХ ст. Рассмотрены рисунки, выполненные автором на
основании живописных художественных памятников предыдущих
столетий. Аналитическое исследование произведений
живописи проведено в контексте многоаспектной программы изучения духовной и материальной культуры народа.
Определен индивидуальный вклад художника в решение
актуальных проблем художественной жизни.